Ehlers-Danlos syndrome in a crossbreed cat - Palumbo, Mariana Isa Poci; Caramalac, Silvana Marques; Caramalac, Simone Marques; Barbosa, Carolynne Ferreira; Ferreira, Julia Franco [UNESP]; de Oliveira-Filho, Jose Paes [UNESP]; Borges, Alexandre Secorun [UNESP] (FapUNIFESP (SciELO), 2022)
The Ehlers-Danlos syndrome (EDS) consists of a group of diseases characterized by defective collagen production or failure in its organization, resulting in changes in the strength and extensibility of connective tissue. This report describes the dermatological and histological findings observed in a 3-month-old crossbreed cat with rupture and detachment of skin in the thoracic limb and rupture of the skin in the cervical region. Upon dermatological examination, the cat presented fragile and hyperextensible skin in the cervical region and a skin extensibility index of 21%. Histopathological evaluation of the skin specimens revealed evident disorganization of collagen bundles in dermis and in the Masson’s trichrome staining, follicular dysplasia was found. The presumptive diagnosis of EDS was made based on the clinical and histopathological findings. Sanger sequencing did not detect any mutated alleles for the c.3420delG mutation in COL5A1 gene, which was an autosomal dominant mutation previously been associated with Ehlers-Danlos syndrome in cats. The absence of this mutation in the reported cat suggests that other mutation may also be responsible for the development of cutaneous asthenia in this or maybe other genes related to collagen metabolism.
Síndrome de Ehlers-Danlos em um gato mestiço
Keywords: collagen; dermatology; laceration; mutation; sequencing